Somatosensory space abridged: rapid change in tactile localization using a motion stimulus. - Tatjana Seizova-Cajic (Public Library of Science (PLoS), 2014)
Introduction Organization of tactile input into somatotopic maps enables us to localize stimuli on the skin. Temporal relationships between stimuli are important in maintaining the maps and influence perceived locations of discrete stimuli. This points to the spatiotemporal stimulation sequences experienced as motion as a potential powerful organizing principle for spatial maps. We ask whether continuity of the motion determines perceived location of areas in the motion path using a novel tactile stimulus designed to 'convince' the brain that a patch of skin does not exist by rapidly skipping over it. Method Two brushes, fixed 9 cm apart, moved back and forth along the forearm (at 14.5 cm s-1), crossing a 10-cm long 'occluder', which prevented skin stimulation in the middle of the motion path. Crucially, only one brush contacted the skin at any one time, and the occluder was traversed almost instantaneously. Participants pointed with the other arm towards the felt location of the brush when it was briefly halted during repetitive motion, and also reported where they felt they had been brushed. Results Participants did not report the 10-cm gap in stimulation - the motion path was perceptually completed. Pointing results showed that brush path was 'abridged': locations immediately on either side of the occluder, as well as location at the ends of the brush path, were perceived to be >3 cm closer to each other than in the control condition (F(1,9) = 7.19; p = .025 and F(1,9) = 6.02, p = .037 respectively). This bias increased with prolonged stimulation. Conclusions An illusion of completion induced by our Abridging stimulus is accompanied by gross mislocalization, suggesting that motion determines perceived locations. The effect reveals the operation of Gestalt principles in touch and suggests the existence of dynamic maps that quickly adjust to the current input pattern.